Ewing’s Sarcoma of the Calcaneum - Sherif, P Ajmal; Santa, A (Indian Journal of Medical and Paediatric Oncology, 2017)
Ewing's sarcoma of the calcaneum is rare. Radiological features of this tumor can be misinterpreted as other benign bone tumors due to its rarity. The overall prognosis of Ewing's sarcoma of calcaneum is inferiorcompared to other sites of this tumor. Hence, these tumors should have extensive radiological evaluation and histological confirmation as misdiagnosis and treatment delays will have detrimental outcomes.
Keywords: Calcaneum; ewing sarcoma; magnetic resonance imaging